Development theories and methods of fracture-vug carbonate reservoirs - LI, YANG (ELSEVIER ACADEMIC Press, 2017)
Development Theories and Methods of Fracture-Vug Carbonate Reservoirs explores the theories and methods for successful development of a fracture-vug reservoir by presenting the developmental strategies used in the Tahe oilfield. Some of the theories and methods of developing the Tahe fracture-vug reservoirs have been inspired by two China national research projects: The 'Basic research on development of fracture-vug carbonate reservoirs' (2006-2010), and the 'Basic research on production mechanism and oil recovery enhancement of fracture-vugcarbonate reservoirs' (2011-2015), with support by the National Basic Research Program of China. These theories and methods have facilitated the successful development of the fracture-vug reservoir in the Tahe oilfield, providing effective technologies and inspirations to developing similar reservoirs everywhere.